EFEKTIVITAS MUSIK MOZART DAN EDUKASI AUDIOVISUAL PADA IBU POSTPARTUM BLUES - Panjaitan, Edita; Pinem, Lina Herida; Lastriyanti, Lastriyanti; Hardani, Joelita Tri (Jurnal Mitra Kesehatan, 2024)
Introduction: Postpartum blues is a situation of mood swings that occur in women after childbirth. Postpartum blues can have a long-term mental health impact on the mother. The short-term impact on the mother is the inability to carry out her role as a mother and maternal self-care. The results of EPDS screening in postpartum patients at RSUD. Bekasi patients were detected to have postpartum depression. This condition occurs because of the focus on postpartum physiological conditions.  One of the treatments that can be given to postpartum mothers is to provide Mozart music relaxation therapy and audiovisual education to respondents. Methods: The research design used is one group pre-post test design method with pre experiment research design. The population in this study were 80 postpartum mothers with inclusion of Postpartum Blues.  Results: analysis of research data shows that there is an average difference (mean) between the pre-test and post-test scores of Mozart music therapy intervention and audiovisual education to overcome postpartum blues, with an average pre-test of 14.44 and an average post-test of 11.13. Conclusion: Mozart music therapy and audiovisual education reduce the EPDS score of postpartum mothers. There is a significant difference between postpartum blues mothers before and after being given the intervention of Mozart Music therapy and Audiovisual Education for postpartum blues. Mozart music therapy and audiovisual education can be applied in the management of postpartum blues.